High power gallium nitride light-emitting diodes for efficient solid state lighting and displays - Ji, Yun (2014)
Nitride based light-emitting diodes (LEDs) are considered to be the next generation lighting source, owing to their superior advantages including high brightness, high energy conversion efficiency, long life span, compact size, fast response, and low maintenance cost. Tremendous work has been devoted to improving the performance of InGaN/GaN multiple quantum well LEDs in the past decades. The GaN based white LED has currently achieved reasonably high efficacy and displays a huge potential of replacing the incandescent and fluorescent lamps in the current market. However, the performance of InGaN/GaN LED light sources is still limited by some technical issues. One of the challenges is to reduce the efficiency droop, the phenomenon of reduction of external quantum efficiency at high current levels, such that the device could maintain high luminous efficacy for high brightness lighting applications. The root cause of the efficiency droop is still under debate, although there have been more convincing reports lately. Also, the lighting source should provide high chromaticity quality comparable to the conventional lighting sources to generate comfortable visual perception. Tremendous research work has been contributed to the improvement of InGaN/GaN LED lighting quality.